2014
DOI: 10.1039/c4sm00652f
|View full text |Cite
|
Sign up to set email alerts
|

Wrapping/unwrapping transition of double-stranded DNA in DNA–nanosphere complexes induced by multivalent anions

Abstract: Wrapping and unwrapping behaviors of double-stranded DNA around a positively charged nanosphere in solution are studied by using the coarse-grained molecular dynamics (CGMD) simulation method. When monovalent, divalent and trivalent anions are added to the DNA-nanosphere complex solution, double-stranded DNA binds with a nanosphere owing to strong electrostatic attraction. However, when tetravalent anions are added to the DNA-nanosphere complex solution, local charge inversion is observed for a high anion conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Computer simulations have been used to investigate the binding of double-stranded DNA with various associating molecules, including proteins, NPs, dendrimers, and polyamines. Albeit invaluable, MD simulations based on all-atom models are time-consuming and computationally expensive. Therefore, the length of DNA fragments considered in MD simulations is typically no longer than 50 bps, which is too short to facilitate bending and wrapping around a cationic NP, except for a few examples .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Computer simulations have been used to investigate the binding of double-stranded DNA with various associating molecules, including proteins, NPs, dendrimers, and polyamines. Albeit invaluable, MD simulations based on all-atom models are time-consuming and computationally expensive. Therefore, the length of DNA fragments considered in MD simulations is typically no longer than 50 bps, which is too short to facilitate bending and wrapping around a cationic NP, except for a few examples .…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been several atomistic MD simulations employing DNA fragments of ∼150 bps, these studies focused on the stability and structural features of nucleosomes (in which the DNA fragment is already wrapped around the histone protein complex) but not on the dynamic process of DNA binding and wrapping. The use of CG models can be an alternative to investigate complex formation between DNA and binding molecules by enabling relatively longer and larger scales of MD simulations. , However, depending on the coarse-graining philosophy, CG models have lists of specific features to determine the model most appropriate to answer specific questions. Among several CG models of DNA, the Martini DNA model is chosen in this work to investigate the effect of DNA flexibility on the complex formation of a cationic NP and a DNA fragment.…”
Section: Introductionmentioning
confidence: 99%
“…Complex formations of a double-stranded DNA with associating molecules such as proteins, NPs, dendrimers, and polyamines have been investigated extensively using computer simulations with various models at different scales. ,,,, MD simulations using all-atom models have provided detailed information on DNA binding with proteins and NPs. However, all-atom MD simulations are too time-consuming and computationally demanding to investigate the dynamic process of DNA bending and wrapping around proteins and NPs, except for a few recent works. , Simple physics-based models of DNA and NPs have also been used to investigate DNA bending and wrapping around a cationic NP, where DNA is modeled as a semiflexible polymer chain and NP as a charged sphere. ,,,, Due to the simplicity of the molecular description, simulations of long-time and large-scale processes concerning DNA wrapping have been enabled. In particular, by using a polymer chain model of DNA with flexibility variation, it was shown that a cationic NP wrapped around by DNA rolls along the DNA from less flexible to more flexible regions to reduce the elastic energy of DNA bending. , However, several critical assumptions were made regarding the molecular interactions of DNA and an NP.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, CG models of DNA and NPs can be used to investigate the complex formation, where longer-time and larger-scale simulations are enabled compared with all-atom MD simulations. In these models, more detailed information on DNA–NP interactions is provided compared to simulations with simple physics-based models of DNA and NPs.…”
Section: Introductionmentioning
confidence: 99%
“…[32] Aninalem et al have pointed out that the salt concentration has a strong influence on the aggregation structure of DNA/PAMAM dendrimer complexes. [33] As salt concentrations have a strong influence on the phase behaviors of DNA chains in solutions, [34,35] we will investigate the decondensation behavior of DNA at various concentrations of monovalent, divalent, and trivalent salt cations in the presence of short cationic chains in solutions. Based on the charge distributions around the DNA chains, we provide a possible explanation for the simulation results.…”
Section: Introductionmentioning
confidence: 99%